Corporate punishment: A proposal - Rafalko, Robert J. (Journal of business ethics, 1989)
“Corporate Punishment: A Proposal” is an exercise in logic and creative thinking. I shall argue that no good reasons exist for the supposition that corporations have rights independent of the rights and interests of the persons they serve and that the error of treating corporations as though they do have autonomous rights derives from a sloppy argument from analogy. I shall further argue that the analogy of corporations to citizens, though pushed too far by some courts and lawmakers, remains a useful analogy if its logical relations can be cleaned up and clarified. Finally, I shall conclude this essay by employing the refurbished analogy in such a way that it yields a proposal for more effective criminal punishment for corporate wrongdoing.